Assessing Fracture Intensity and Petrophysical Properties in the Jatibarang Formation's Volcanic Reservoirs, North West Java Basin - Baihaqie, Qosha; Rohmana, Rian Cahya; Atmoko, Widi (Penerbitan Universitas Trisakti, 2024)
Volcanic rock reservoirs, characterized by fractures in their formations, have gained attention in Indonesia due to their oil content, particularly in the Jatibarang Formation in West Java. This study focuses on four wells in the West Java Basin containing the Jatibarang Formation, aiming to determine fracture intensity using conventional log data and to perform petrophysical analysis. The research employs well log, mud log, and core data, utilizing qualitative analysis to identify potential reservoir zones and quantitative analysis to calculate fracture intensity and petrophysical properties. The results show that fractures in the Jatibarang Formation can be identified through fracture intensity analysis using conventional log data (MSFL, RHOB, Caliper, PEF, and DT). Fracture intensity calculations were only carried out on the QB-3 well because the other wells did not have complete log data. The results of the fracture intensity analysis showed that the fractures that occurred in the QB-3 well had 1-23%. Petrophysical analysis of the four wells reveals that the cutoff values for clay volume (50%), porosity (10%), and water saturation (70%) indicate potential candidates for further reservoir research. The QB-3 well has seven potential zones with a fracture index value of more than 10%. Permeability in wells QB-3 and QB-4 is more than 60 mD, making these four wells potential candidates for further research on volcanic rock reservoirs.